'Ain't I a feminist?': the politics of gender violence, anti-violence, and education in Oakland, CA. Issue 4 (3rd April 2017) - Jibrin, Rekia
Abstract: This article focuses on the ways gender violence politics become reduced to liberal narratives of victimization in contemporary U.S. deployment of feminist identity politics, within academic and activist discourses. Such victimization narratives, I argue, exploit suffering and reproduce social stratification between a growing middle class in the academy and poor black people outside of it. This article draws from moments in California's Bay area when questions of feminism, gender violence, and anti-violence in schools arose. In each case, left feminists had an opportunity to reshape these questions towards new political paradigms and new academic discourses. Instead, amidst the 'safety' of left discourse and practice, each moment confronted contradictory silences that called into question such 'safety' and made generative political movement impossible. I analyze the dynamics of this silencing as constitutive of the co-optation of feminist identity politics within a capitalist university that reproduces an oppressive race and class order. We face a problem of language to adequately explain and disrupt the incapacity for collective social change that victimhood, identity politics, and reformism have produced. Each instance I present function as moments of history making from which we may reflect and strategize forward movement against capitalist oppression and racial dehumanization.